Anti-nociceptive effects of oxytocin receptor modulation in healthy volunteers–A randomized, double-blinded, placebo-controlled study - Biurrun Manresa, José Alberto (2021)
Background: There is increasing evidence for oxytocin as a neurotransmitter in spinal nociceptive processes. Hypothalamic oxytocinergic neurons project to the spinal dorsal horn, where they activate GABA-ergic inhibitory interneurons. The present study tested whether the long-acting oxytocin-analogue carbetocin has anti-nociceptive effects in multi-modal experimental pain in humans. Methods: Twenty-five male volunteers received carbetocin 100 mcg and placebo (0.9% NaCl) on two different sessions in a randomized, double-blinded, cross-over design. Multi-modal quantitative sensory testing (QST) including a model of capsaicin-induced hyperalgesia and allodynia were performed at baseline and at 10, 60 and 120 min after drug administration. QST data were analysed using mixed linear and logistic regression models. Carbetocin plasma concentrations and oxytocin receptor genotypes were quantified and assessed in an exploratory fashion. Results: An anti-nociceptive effect of carbetocin was observed on intramuscular electrical temporal summation (estimated difference: 1.26 mA, 95% CI 1.01 to 1.56 mA, p =.04) and single-stimulus electrical pain thresholds (estimated difference: 1.21 mA, 95% CI 1.0 to 1.47 mA, p =.05). Furthermore, the area of capsaicin-induced allodynia was reduced after carbetocin compared to placebo (estimated difference: −6.5 cm2, 95% CI −9.8 to −3.2 cm2, p <.001). Conclusions: This study provides evidence of an anti-nociceptive effect of carbetocin on experimental pain in humans. Significance: This study provides evidence of the anti-nociceptive effect of intravenous administration of the oxytocin agonist carbetocin in healthy male volunteers.